Lichen Sclerosus of the Labial Mucosa: A Case Report and Literature Review - Phuwaraks K; Rutnin S; Suchonwanit P (Dove Medical Press, 2024)
Koramon Phuwaraks, Suthinee Rutnin, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat Suchonwanit, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 Ext 4, Email poonkiat@hotmail.comAbstract: Lichen sclerosus (LS) is an uncommon, chronic, inflammatory mucocutaneous disorder found predominantly in females with unknown etiology. It presents as a white sclerotic plaque commonly located on the anogenital area. Extragenital LS is less prevalent, and LS affecting the oral mucosa is extremely rare, with only 39 biopsy-confirmed cases reported in the literature. Due to its several mimicking conditions, histological examination is usually required for a definitive diagnosis, particularly in patients with oral LS. Current evidence-based treatment recommendations for oral LS are unavailable; however, most cases tend to improve after treatment with topical or intralesional corticosteroids. We report a case of a 58-year-old female referred from the otolaryngology department for evaluating an asymptomatic whitish sclerotic plaque on the lower lip mucosa that had existed for 1 year. Following a punch biopsy, the patient was diagnosed with LS of labial mucosa. The condition improved after 2 months of treatment with topical and intralesional corticosteroids. The present case report raises awareness in recognizing oral LS and contributes to knowledge of this rare disorder.Keywords: extragenital lichen sclerosus, lichen sclerosus et atrophicus, lichenoid dermatitis, lip, oral mucosa, sclerosis